Light-induced reversible reorganizations in closed Type II reaction centre complexes: physiological roles and physical mechanisms - Sipka, G; Nagy, L; Magyar, M; Akhtar, P; Shen, J-R; Holzwarth, A R; Lambrev, P H; Garab, G (Open biology, 2022)
The purpose of this review is to outline our understanding of the nature, mechanism and physiological significance of light-induced reversible reorganizations in closed Type II reaction centre (RC) complexes. In the so-called 'closed' state, purple bacterial RC (bRC) and photosystem II (PSII) RC complexes are incapable of generating additional stable charge separation. Yet, upon continued excitation they display well-discernible changes in their photophysical and photochemical parameters. Substantial stabilization of their charge-separated states has been thoroughly documented-uncovering light-induced reorganizations in closed RCs and revealing their physiological importance in gradually optimizing the operation of the photosynthetic machinery during the dark-to-light transition. A range of subtle light-induced conformational changes has indeed been detected experimentally in different laboratories using different bRC and PSII-containing preparations. In general, the presently available data strongly suggest similar structural dynamics of closed bRC and PSII RC complexes, and similar physical mechanisms, in which dielectric relaxation processes and structural memory effects of proteins are proposed to play important roles.
Keywords: Photosynthesis; Photosystem II Protein Complex; fotosystém II (proteinový komplex); Marcus theory; dielectric relaxation; purple bacterial reaction centre; photosystem II; fotosyntéza; chlorophyll fluorescence; dynamics and structural memory of proteins